Efek Menonton Tayangan Video Ciri – Ciri Berita Hoaks Terhadap Tingkat Pengetahuan Remaja Tentang Berita Hoaks - Mahardika Indra Pratama; Djoko Setyabudi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
News hoax is news that contains the meaning of a lie or the news is not sourced. Online media portals that have arisen in pursuit of speed and profit news, do not care about the authenticity of the data and news sources. Data from the Ministry of Communication and Information stated that in January 2019 more than 70 hoax news issues were detected. This number beats the total number of a hoax that occurred during 2018. The number of hoax news during 2018 was only around 60 issues. So with this case prevention needs to be held so that news hoax is not widespread and many people are more critical in choosing information.This study aims to determine the effect of the use of video media on the level of knowledge of hoax news on teenagers. This type of research is an experiment and then involved teen participants aged 18-21 years in Semarang. The study participants numbered 60 people who were then given a questionnaire conducted twice, namely pretest and posttest. Analysis of data using the T-test. Based on the results of the t-test it was known that the average pretest of the experimental group was 61.50 then after the treatment of video screening and the results of the post-test were 88.97 increasing to 27.79. Furthermore, based on the hypothesis test, it shows a sig value of 0,000 <0.05 so that it can be stated that there is a significant increase in the score of the experimental group or that is treated by a video show. In conclusion, the use of video media has the effect of increasing adolescent knowledge about news hooks.